2017
DOI: 10.1007/s11199-017-0858-4
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ Influence on Infants’ Gender-Typed Toy Preferences

Abstract: Gender socialization influences children at early ages, shaping their developing identities. The toys provided by parents deliver some of the earliest gender-based messages by encouraging children to engage in activities associated with, for example, dolls and trucks. In the current study, we measured the influence of parental socialization by assessing 5-and 12 ½-month-old infants' exposure to dolls and trucks and by experimentally manipulating parents' encouragement to play with these toys. We found that inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 108 publications
1
27
0
4
Order By: Relevance
“…Bu sonuca, okul öncesi dönemde çocuklarla en çok vakit geçiren aile ve öğretmenlerin değerlendirmeleri sonucu ulaşılmıştır. Çalışmamızla paralel olarak, yapılan bir çalışmada çocukların oyuncak tercihlerinin sosyal uyum davranışlarını olumlu etkilediği belirtilmiştir (20) . Türkiye'de 1986-2013 yılları arasında okul öncesinde oyun ile ilgili yapılan lisansüstü tezlerin incelenmesi amacıyla yapılan çalışmada da oyun davranışının sosyal duygusal gelişimi sağlamada ve kişilerarası iletişim üzerinde etkili olduğu bildirilmiştir.…”
Section: Discussionunclassified
“…Bu sonuca, okul öncesi dönemde çocuklarla en çok vakit geçiren aile ve öğretmenlerin değerlendirmeleri sonucu ulaşılmıştır. Çalışmamızla paralel olarak, yapılan bir çalışmada çocukların oyuncak tercihlerinin sosyal uyum davranışlarını olumlu etkilediği belirtilmiştir (20) . Türkiye'de 1986-2013 yılları arasında okul öncesinde oyun ile ilgili yapılan lisansüstü tezlerin incelenmesi amacıyla yapılan çalışmada da oyun davranışının sosyal duygusal gelişimi sağlamada ve kişilerarası iletişim üzerinde etkili olduğu bildirilmiştir.…”
Section: Discussionunclassified
“…Moving to slightly older infants, Lutchmaya and Baron-Cohen (2002) found that at 12 months, male infants paid more attention to moving cars, whereas female infants paid more attention to moving faces. A recent study by Boe and Woods (2018) also found male infants aged 12 months showed a preference for trucks over dolls in a grasping task, whereas 12-month-old female infants showed no such preference. Similarly, an observational study during a laboratory play session reported that female but not male infants aged 10-18 months interact longer with dolls than other toys such as trucks (Roopnarine, 1986).…”
Section: Introductionmentioning
confidence: 89%
“…With respect to the emergence of infant gender-specific toy preference, previous studies found no gender-specific or general toy preferences when comparing toys with faced stimuli among 5-montholds (Boe & Woods, 2018;Escudero et al, 2013) and even 12-month-olds (Jadva et al, 2010;Servin et al, 1999). This indicates experience may be required for infants to develop robust gender-specific toy preference in the second year after birth.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations